PENYANDERAAN PENDUDUK SIPIL OLEH PASUKAN TALIBAN (2016): TINJAUAN HUKUM HUMANITER INTERNASIONAL - Atsyilla Salsabilla; Arlina Permanasari (Reformasi Hukum Trisakti, 2021)
The Non-International Armed Conflict between Afghanistan and the Taliban has been triggering the hostage-taking of civilians that occurred in Afghanistan in 2016. Based on Article 3 of the Common Article of the 1949 Geneva Convention, hostage-taking of civilians is prohibited. The formulation of the problem in this research is how the aspects of international humanitarian law on the hostage-taking of civilians committed by the Taliban in Afghanistan in 2016 and what are the legal consequences for the Taliban. This research is a normative legal research by referring to the norms in Article 3 of the Geneva Convention and Article 6 of the 1977 Additional Protocol II. Secondary data processing is carried out qualitatively, drawing conclusions deductively. Based on the results of research, discussion, and conclusions, the commentary of Article 3 of the 1949 Geneva Convention has laid the foundation for Afghanistan to try and punish the Taliban for taking hostages. The general provisions of Article 3 are complemented by the provisions in Article 6 of Additional Protocol II 1977 which states that the settlement of hostage cases must be carried out in accordance with the applicable Afghan national law, in this case the Afghanistan Penal Code 1976.